Microbiota, metabolic profiles and immune biomarkers in infants receiving formula with added bovine milk fat globule membrane: a randomized, controlled trial - Christensen, Chloe; Kok, Car Reen; Harris, Cheryl L.; Moore, Nancy; Wampler, Jennifer L.; Zhuang, Weihong; Wu, Steven S.; Hutkins, Robert; Izard, Jacques; Auchtung, Jennifer M. (Frontiers in Nutrition, 2024)
Introduction: Few studies have evaluated the effects of milk fat globule membrane (MFGM) on microbiota and immune markers in early infant nutrition. Methods: In this double-blind randomized study, infants (7-18 days of age) received either bovine milk-based infant formula (Control) or similar formula with an added source (5g/L) of bovine MFGM (INV-MFGM) for 60 days. A reference group received mother’s own human milk over the same period (HM). Oral and stool samples were collected (Baseline and Day 60) to evaluate microbiota, immune markers, and metabolites. Results: At Day 60, stool bacterial diversity and richness were higher in formula groups vs HM, as were Bifidobacterium bifidum and B. catenulatum abundance. Compared to HM, stool pH was higher in Control, while acetate, propionate, isovalerate, and total short- and branched-chain fatty acids were higher in INV-MFGM. Butyrate and lactate increased for INV-MFGM from baseline to Day 60. No group differences in oral microbiota or immune markers (α- and β-defensin, calprotectin, or sIgA) were detected, although sIgA increased over time in all study groups. Added bovine MFGM in infant formula modulated stool microbiota and short- and branched-chain fatty acids compared to human milk; changes were modest relative to control formula. Discussion: Overall, distinct patterns of stool metabolites and microbiota development were observed based on early nutrition. Clinical trial registration: ClinicalTrials.gov, identifier NCT04059666.